Tai Chi as a Simple Exercise to Increase Immunity and Psychological Well-being: Narrative Review - Nita Fitria; Tati Sumarni; Diana Kusuma Astuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: COVID-19 is a virus that attacks the human respiratory system and is more at risk of attacking someone with a low immunity level. Apart from having a physical impact, COVID-19 also has a psychological impact. Those impacts need efforts to increase immunity and psychological well-being. The effort that we can make is through a sports program. The right kind of exercise is a moderate-intensity exercise that involves thoughts, emotions, and physical sensations, such as yoga, meditation, and Tai Chi. Purpose: This article aims to analyze the effect of Tai Chi on increasing immunity and psychological well-being in the New Normal era. Methods: This article uses the narrative review method with the keyword "(People OR Adult OR Young Adult AND Tai Chi AND Immunity OR Psychological well being). The databases used were Cochrane, EBSCO, Pubmed, and Taylor Francis. 9 articles were obtained, which were then re-selected based on predetermined criteria. Article selection is also carried out using JBI to ensure the articles' quality is appropriate. Results: A literature search resulted in 9 articles showing that Tai Chi has benefits for improving psychological well-being, immunity, and physical function. Conclusion: Tai Chi can improve immunity, physical functioning, and psychological well-being when it occurs regularly. This benefit helps overcome the impact and prevention of COVID-19. Tai Chi programs are relatively easy to do at home and do not need to spend money. Apply quickly and become an effective solution. Abstrak: Latar Belakang: COVID-19 merupakan virus yang menyerang sistem pernapasan manusia dan lebih beresiko menyerang seseorang yang memiliki tingkat imunitas rendah. Selain berdampak pada fisik, COVID-19 juga berdampak pada psikologis. Hal tersebut menunjukan bahwa diperlukan adanya upaya peningkatan imunitas dan kesejahteraan psikologis. Peningkatan imunitas dan kesejahteraan psikologis dapat dilakukan melalui program olahraga. Olahraga yang tepat adalah olahraga dengan intensitas sedang yang melibatkan pikiran, emosi, dan sensasi fisik seperti yoga, meditasi, dan Tai Chi. Tujuan: Penulisan artikel ini bertujuan untuk menganalisis pengaruh Tai Chi terhadap peningkatan imunitas dan peningkatan kesejahteraan psikologis di era Adaptasi Kebiasaan Baru (AKB). Metode: Penulisan artikel menggunakan metode narative review dengan kata kunci “(People OR Adult OR Young Adult AND Tai Chi AND Immunity OR Psychological well being). Database yang digunakan yaitu Cochrane, EBSCO, Pubmed, dan Taylor Francis. Hasil: Pencarian litertaurue menghasilkan 9 artikel yang menunjukan bahwa Tai Chi memiliki manfaat untuk meningkatkan kesejahteraan psikologis, imunitas, dan meningkatkan fungsi fisik. Kesimpulan: Manfaat Tai Chi berguna untuk mengatasi dampak dan pencegahan penyakit COVID-19. Kesimpulan Program Tai Chi relatif mudah dilakukan di rumah sehingga mudah diaplikasikan dan menjadi solusi yang efektif.